Understanding the psychology of psychological help-seeking patterns in community and barriers to it: A brief discussion - Maiti, Tanay; Paul, Madorina; Agarwal, Sikha; Tiwari, Chandra Sekhar (Eastern Journal of Medical Sciences, 2017)
Although help seeking is prominent at the time of distress due to medical or surgical illnesses, it is not the same when it comes for psychological causes. The psychology of such behavior or available service use is often complex and depends on variable factors. Proper pathway of care right from the community to tertiary care settings is necessary including understanding the various psychosocial barriers which may cause hindrance at any step of care.